2023
DOI: 10.26480/fabm.01.2023.47.52
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Margin and Income Disparity Among Pearl Millet Traders

Godfrey C. Onuwa,
Salawu A. Jibril,
Sunday S. Mailumo

Abstract: This study analyzed the determinants of market margin and income disparity among Pearl Millet traders at Tilden Fulani Main Market, Toro, Bauchi State, Nigeria. A multistage technique was used to collect data from 90 respondents. Descriptive statistics, Market margin and efficiency ratio, regression analysis and Gini Coefficient index were analytical techniques adopted. The mean age, years spent in school, household size, trading experience and quantity of bags sold were 39 years, 6 years, 8 people, 10 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Hence, the number of years a respondent spends performing any marketing function directly influences their marketing experience and, thus, improves efficiency in commodity marketing over time. This result is consistent with Onuwa et al (2023) and Onunka et al (2011), who also reported in their respective studies on the determinants of marketing margins and profitability of African Aubergine marketing a positive correlation between the respondents' marketing experience and profitability in agro-commodity marketing.…”
Section: Determinants Of Marketing Marginsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, the number of years a respondent spends performing any marketing function directly influences their marketing experience and, thus, improves efficiency in commodity marketing over time. This result is consistent with Onuwa et al (2023) and Onunka et al (2011), who also reported in their respective studies on the determinants of marketing margins and profitability of African Aubergine marketing a positive correlation between the respondents' marketing experience and profitability in agro-commodity marketing.…”
Section: Determinants Of Marketing Marginsupporting
confidence: 91%
“…Agricultural markets can be defined as a set of conditions and activities that facilitate trade transactions whether or not the parties physically meet (Onuwa et al, 2023, Agba, 2006. 'Market' denotes the interaction of the forces of demand and supply, irrespective of the physical location of buyers and sellers.…”
Section: Introductionmentioning
confidence: 99%